Surrealism and photography in 1930s Japan - Stojković Jelena, author.
1 online resource (272 pages)
Keywords: Despite the censorship of dissident material during the decade between the Manchurian Incident of 1931 and the outbreak of the Pacific War in 1941, a number of photographers across Japan produced a versatile body of Surrealist work. In a pioneering study of their practice, Jelena Stojkovic draws on primary sources and extensive archival research and maps out art historical and critical contexts relevant to the apprehension of this rich photographic output, most of which is previously unseen outside of its country of origin. The volume is an essential resource in the fields of Surrealism and Japanese history of art, for researchers and students of historical avant-gardes and photography, as well as forreaders interested in visual culture.